Meningkatkan Kesadaran Toleransi dan Keberagaman Serta Mengembangkan Program Pembangunan Masyarakat Inklusif Melalui Sarasehan - Saputro, Darmanto; Sukmana, Oman (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The social, political, and religious dynamics in contemporary Indonesia are often marked by increasing identity polarization and a decline in respect for differences among citizens, thus emphasizing the urgency of raising awareness of tolerance and diversity as the main foundation for building an inclusive society. When linked to inclusive community development, tolerance and diversity become essential prerequisites for creating a social space that accommodates the active participation of all citizens. A seminar, as a participatory dialogue method, offers a safe and egalitarian space for various stakeholders to exchange views, discuss, and find common ground on sensitive issues related to religion and politics. The seminar has successfully served as a catalyst for change, shifting participants' thinking and behavior towards a more positive direction. Certainly, there needs to be follow-up in the form of concrete, implementable programs, such as further seminars, community formation, or collaborative initiatives driven by participants to translate that awareness into real action. The expected structural changes are the strengthening of tolerance and diversity awareness internalized in the norms and daily life practices of society, reflecting the sustainable actualization of good values.